O não-lugar do lugar da escola: sentidos produzidos por jovens de 15 a 17 anos na Educação de Jovens e Adultos - Maria Clemência de Fátima Silva (2019)
This thesis analyzes the meanings of school experience among 15 to 17-year old’s who remain in elementary school. We started from the hypothesis that the permanence of young people in this phase of Basic Education would be related to a larger plot that involves life histories, different belongings, different inequalities, worldviews, unique experiences, sociability, different social contexts, interfering in the warp of the multiple school meanings. In search of understanding such warps, we comprehend the research problem by examining the meanings these young people attribute to their school experiences. This is a qualitative research carried out in a municipal school in Belo Horizonte, located on the outskirts of the city, which initially comprised a panoramic observation of the classes with the highest concentration of young people, from October to December 2016, continuing throughout 2017, with focused and systematic follow-up of young students in a youth EJA class. During the research process, in-depth interviews, verification of school documents and informal conversations were also conducted. Data analysis was conducted by the interlace between readings on youth condition and youth and adult education, from a decolonial perspective. It is concluded that young people and their families, in the framework of their subordinated lives, build insurgent ways of confronting contexts of violation and deprivation of rights in their different dimensions - class, race, gender - in which the school assumes plural and diversified meanings, according to the singularities of scholar trajectories, in a perspective of resistance forged from non-place in school.